Food perception at lunchtime does not depend on the nutritional and perceived characteristics of breakfast. (4th July 2018) - Rosi, Alice; Mena, Pedro; Scazzina, Francesca; Marino, Barbara; Daneyko, Olga; Fasano, Fabrizio; Di Dio, Cinzia; Riggio, Lucia; Brighenti, Furio
Abstract: Breakfast consumption can entail nutritional advantages positively affecting food choices. This study investigated the effect of minor changes in breakfast composition on the perceived attributes of foods, both at breakfast and at lunchtime. Four breakfasts were defined considering nutritional and perceptual factors. Three breakfasts varied just for a single cereal-based chocolate-containing food item, while a control breakfast mimicked fasting conditions. Breakfast perception was assessed before and after consumption. Subjects rated breakfast energy content on the basis of single items, while judged breakfast healthiness as a whole, suggesting that the combination of different ingredients can modify the perceived health value of foods. Additionally, 4 h after breakfast, a perceptual evaluation of lunch-related food images was performed, without differences among breakfasts. This study extends current knowledge on the relationship between subjective perceptual attributes and objective energy value and food composition, as well as on breakfast impact on food perception at lunchtime. Graphical Abstract: